(untitled) (International Journal of Geoscience, Engineering and Technology, 2020)
Ensuring water quality is extremely important for human health. In hemodialysis, for example, the water is used to produce the dialysis solution, therefore, it is necessary to ensure the chemical and microbiological quality of the water through the monitoring and maintenance from equipments to provide improvements in the life condition of the chronic renal patient, in addition to reducing the hospitalizations and comorbidities. Ensuring the quality of water for human consumption is also extremely important, since water unfit for consumption can lead to the accumulation of inorganic contaminants, especially in people with kidney failure and chronic kidney disease. Considering the importance of ensuring water quality, this work, under development, aims to evaluate the toxicological exposure of the chemical element aluminum in patients who made treatment of hemodialysis in a macroregional hospital unit from the Vale do Mucuri and Jequitinhonha, and correlate her with the water quality.